Ultrasonic anisotropy in magnetic liquids - HORNOWSKI, T.; SKUMIEL, A.; ŁABOWSKI, M. (Archives of Acoustics, 1996)
Experimental results for magnetic field influence on the ultrasonic anisotropy in magnetic fluids are reported. The measurements have been carried out for the frequency 3.37 MHz, at the temperature 20°C and magnetic field of strength B = 100 mT, 200 mT and 500 mT. The results were analyzed in terms of Gotoh/Chung theory and Taketomi theory. The former was found to exhibit a lack of inner consistency while the latter gives reliable values of the physical parameters obtained by best-fit procedure.